The Cost of Regulatory Compliance in the United States - Trebbi, Francesco; Zhang, Miao Ben; Simkovic, Michael (Review of Financial Studies, 2026)
Abstract A key question for studying business dynamism is whether the costs of regulatory compliance fall homogeneously on small and large businesses. Using comprehensive establishment-level occupational microdata and occupation task information, we quantify a firm’s compliance costs as the share of wage bill for performing regulatory compliance tasks (RegIndex). We reveal an inverted-U relationship between firms’ RegIndex and their size: On average, RegIndex for mid-sized firms with around 500 employees is about 47% greater than that of the smallest firms and 18% greater than that of the largest firms. We further develop a shift-share methodology to disentangle the influence of regulatory requirements and enforcement on driving firms’ compliance costs.